«Io ti abbandono, o Franco, il paradiso». Sul carteggio tra Cesare Cases e Franco Fortini - Spampinato, Salvatore (L’ospite ingrato, 2024)
The essay is a study of the decades-long correspondence between Cesare Cases and Franco Fortini preserved in the archives of the Centro Studi Franco Fortini. In particular, the analysis focuses on five key issues that run through the entire exchange: 1) the testimonies of the two intellectuals during some important historical events of the second Twentieth Century, such as the crisis of ‘56, Vietnam War and Maoist China; 2) some significant comments and positions taken in the literary field; 3) the singular poetic compositions in a satirical-epigrammatic style that the two exchanged; 4) work as translators and mediators of German culture (focusing on Bertolt Brecht); 5) the uninterrupted dialogue, through De Martino’s writings, around the theme of death and the possibility of Marxism to address it in a systematic way.